Dysphagia: A practical approach - Giuseppina Russo; Caterina Strisciuglio (Elsevier, 2024)
Dysphagia is any disorder of the swallowing process. It can be classified according to the disordered phase of swallowing: oral dysphagia, pharyngeal dysphagia, esophageal dysphagia. Approximately 1% of children in the general population will experience swallowing difficulties, although the incidence is much higher in some clinical populations. Although oropharyngeal dysphagia may be the first symptom of a neuromuscular disorder, gastroesophageal reflux disease (GERD), functional esophageal disorders, and eosinophilic esophagitis are the most common causes of esophageal dysphagia. Treatment and management of dysphagia must be tailored to the clinical characteristics of the individual patient.